AB0315 RETENTION RATE OF ABATACEPT MONOTHERAPY IN AN ITALIAN MULTICENTRIC RHEUMATOID ARTHRITIS COHORT. (2nd June 2020) - Iacono, D.; Pantano, I.; Birra, D.; Scalise, G.; Coscia, M. A.; Messiniti, V.; Loi, G.; Merchionda, A.; Moscato, P.; Ciccia, F.
Abstract : Background: EULAR recommendations focus the importance of Methotrexate (MTX) therapy as a key element in the treatment of patients with Rheumatoid Arthritis (RA), alone as first line therapy and in combination with biological Disease Modifying Anti-rheumatic Drug (bDMARDs). Abatacept (CTLA4-Ig) in Europe is approved for the treatment of moderate to severe active RA in combination with MTX. Several patients, however, discontinue MTX for intolerance, side effects or contraindications, and real-life data demonstrate how, even in patients receiving therapy with MTX, compliance could be suboptimal. The only data on the use of abatacept in monotherapy come from the ORA-Registry, where a worse performance is observed in monotherapy patients. Objectives: To evaluate a multicenter cohort of RA patients treated with Abatacept in patients underwent combined MTX therapy vs monotherapy. Methods: We retrospectively evaluated RA patients, referring to 2 Italian rheumatology centers, treated with Abatacept monotherapy or in combination with MTX. We compared both persistence in therapy and the rate of remission/low disease activity according to Clinical Disease Activity Index (CDAI) between the 2 groups. Results: We enrolled 147 patients, out of them 66 patients were on monotherapy with Abatacept due to intolerance or controindications and 81 in therapy with Abatacept plus MTX. The two cohorts appeared homogeneous in age, gender, disease duration and baseline activity indexes, with the only difference being higher baseline Physician Global assessment (PhGA) values in monotherapy patients. During the follow-up (median duration 24±14 months), the retention rate of Abatacept treatment was 71.2% in MTX patients (median duration 27–15.6 months) and 62.1% in monotherapy patients (median duration 25.2–17.5; p=ns). No differences between the two groups in terms of retention rate, low-disease activity and CDAI remission (log rank p=ns), Breslow p=ns) were detected. Conclusion: In patients with RA with intolerance or contraindication to MTX use, Abatacept monotherapy could be an efficient and safe option even in the long term follow-up. References: [1]Abatacept monotherapy compared with abatacept plus disease-modifying anti-rheumatic drugs in rheumatoid arthritis patients: data from the ORA registry. Truchetet ME et al. Arthritis Res Ther. 2016 Mar 30;18:72. Disclosure of Interests: DANIELA IACONO Speakers bureau: PFIZER, BRISTOL MAYERS SQUIBB, SANOFI, Ilenia Pantano: None declared, domenico birra: None declared, GIUSEPPE SCALISE: None declared, Melania Alessia Coscia: None declared, VALENTINA MESSINITI: None declared, Gabriella Loi: None declared, Anna Merchionda: None declared, Paolo Moscato: None declared, francesco ciccia Grant/research support from: pfizer, novartis, roche, Consultant of: pfizer, novartis, lilly, abbvie, Speakers bureau: pfizer, novartis, lilly, abbvie